Workability dan Sifat Mekanik Self Compacting Geopolimer Concrete (SCGC) - Rita Hardianti Aris; Erniati Bachtiar; Ritnawati Makbul (Litbang Pemas - Universitas Islam Lamongan, 2021)
The purpose of this study was to investigate the relationship between molarity and workability in Self-Compacting Geopolymer Concrete (SCGC), as well as mechanical properties. Compressive strength and split tensile strength tests are used to characterize the mechanical characteristics in this research. Additionally, the study investigates the optimal molarity for self-compacting geopolymer concrete. Fly ash was used in lieu of cement in this research. On new concrete self-compacting geopolymer, workability is determined using the EFNARC standard, which includes the Slump Flow, V-Funnel, and L-Box tests. ASTM 39/C 39M-99 standard is used to determine the compressive strength of self-compacting concrete geopolymer. On new concrete, workability is determined using the EFNARC standard, which comprises the Slump Flow Test, a V-funnel, and an L-Box. The compressive strength of concrete samples is determined according to the ASTM 39/C 39M – 99 standard. The SNI 03-2491-2002 standard is used to determine the split tensile strength of concrete. At the ages of 7, 14, and 28 days, tests were conducted. The findings indicated that new concrete at 11M-13M satisfied the criteria for SCGC workability. The compressive and split tensile strengths of SCGC grow as the concrete ages. In self-compacting geopolymer concrete, the optimal molarity is 13 M.